Evaluasi Mutu Sensoris Makanan Jajanan Berbahan Dasar Sagu Menggunakan Uji Hedonik Dan Uji Mutu Hedonik - Palijama, Syane (Universitas Pattimura, 2025)
Sago is one of Indonesia's local carbohydrate sources that has great potential as a raw material for various food products. This study aims to evaluate several types of sago-based snacks through hedonic tests covering color, aroma, taste and overall appearance (overall appearance) as well as hedonic quality tests covering the level of sweetness, taste and aroma. The hedonic test method and hedonic quality with a scale of 1–5 were used on 5 types of sago-based snacks, namely sago lempeng, sago tumbu, sarut, bagea and kue bangket. The results showed that of the 5 types of sago-based snacks tested, kue bangket and bagea were the products with the highest level of acceptance based on both hedonic tests and hedonic quality tests. Sago lempeng had the lowest level of preference mainly due to its neutral taste and aroma.